Low temperature properties of Ce(Pd1-xAgx) - Kappler, J.P.; Haen, P.; Trovarelli, O.; Sereni, J.G.; Besnus, M.J.; Sereni, Julián (Springer, 1996)
Fil: Trovarelli, O. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina